ANALISIS NILAI MORAL DALAM NOVEL SURAT KECIL UNTUK TUHAN KARYA AGNES DAVONAR - rianti, ulfa; Rahayu, Zona Rida; Halid, Elan (Program Studi Pendidikan Bahasa Indonesia, , Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mahaputra Muhammad Yamin, 2023)
The background of this research is motivated by the existence of moral values ??that are very useful for readers. Little Letter to God, famous for the real life story of a teenage girl who suffered from soft tissue cancer for the first time in Indonesia. This is the background to the research problem which contains moral values, namely the relationship between humans and themselves, the relationship between humans and other humans, the relationship between humans and nature and the relationship between humans and God. The aim of this research is to describe the analysis of moral values ??in the novel Little Letters to God by Agnes Davona. This type of research is qualitative with descriptive methods. Data collection can be done using the following steps: (1) Reading the novel repeatedly to understand the content of the novel to be studied. (2) Code and underline quotes contained in the novel Little Letters for God by Agnes Davonar that contain moral values. (3) Record the data that has been coded in the Novel Little Letters for God by Agnes Davonar. Data analysis is: (1) Read again all the data that has been collected. (2) Classify the data containing Moral Values ??in the novel Surat Kecil untuk God by Agnes Davonar based on the table format in the research instrument. (3) Draw conclusions from data analysis. (4) Write a complete report. The amount of data found was 146 data, so in the novel Small Letters for God by Agnes Davonar, many moral values ??were found, namely the relationship between humans and themselves.